OPTIMIZATION OF OPERATION PROCESSES ADVANCED AIRCRAFT ECONOMIC CRITERIA - Konakhovich , G. F.; Kozlyuk , I. A. (Problems of Informatization and Management, 2005)
The article defines the methodology for the formation of the optimal exchange fund of aircraft products for various options for building a maintenance and repair system in order to develop an integrated approach to optimizing the operation of promising aircraft based on technical and economic criteria for the effectiveness of maintenance and repair.